ISO 9001 internal decertification motivations: exploring barriers and benefits of certification as withdrawal antecedents - Candido, Carlos J. F. (2022)
Thousands of companies worldwide lose their ISO 9001 certification every year. Considering the relevance that this decertification phenomenon has achieved, this study examines the internal motivations for decertification and explores the relationships between motivations and firm's previous certification barriers and benefits. To achieve this purpose, the study develops a partial least squares structural equation model (PLS-SEM) from the literature and estimates the model based on data collected from a sample of 248 certified organisations. Results reveal that the main antecedents of internal decertification motivations are external factors, namely external decertification motivations and external certification barriers. External barriers do not disappear after certification and have a stronger influence on motivations than (lack of) certification benefits. Internal and external benefits have a small effect on motivations, and internal barriers have no significant effect. In addition, the relationship between external barriers and internal decertification motivations is mediated by external motivations. Similarly, the relation between external benefits and internal motivations is mediated by internal benefits. Currently, there are no other studies on the relationship between internal and external decertification motivations, nor studies identifying the antecedents of both motivations. Thus, the research findings constitute novel contributions to the literature and suggest relevant implications for practice.